Household air pollution related to biomass cook stove emissions and its interaction with improved cookstoves - Rebecca Pratiti (AIMS Press, 2021)
Introduction: Household air pollution (HAP) is associated with significant global morbidity and mortality. Newer initiatives including improved cookstove (IC) and cleaner fuels are being implemented to improve HAP effects. Methods: A literature review was conducted for household air pollution related to biomass cookstoves in resource limited countries. In January 2018, we electronically searched the PubMed database for the term cookstoves with no date restrictions. We included cohort, case-control, cross-sectional studies, conference abstracts, editorials, and reviews; studies that assessed the emissions related to cookstove and factors affecting HAP emissions. Results: Twenty-three articles met the objectives of the review. Fine particulate matter with aerodynamic diameter <2.5 µm (PM2.5), carbon monoxide (CO) and polycyclic aromatic hydrocarbons (PAH) are the major HAP emissions. Emission factors are based on the stove and fuel used while the activity is based on cooking practices. Changes in composition and sources of PM2.5 causes modification to its resulting toxicity. Many PAHs and their metabolites released by HAP have carcinogenic, teratogenic and mutagenic potential. Improving ventilation decreases concentrations of PM2.5 and CO in the household air. Few standard tools are available to measure ventilation and continued IC efficacy in long term. Conclusion: Unavailability of tools to measure ventilation and continued IC efficacy in long term affect uniformity and comparability of IC study results. Community education about the health effects of HAP and importance of ventilation in decreasing HAP is an important aspect of public health policy to prevent HAP effects.